The development of shaking tables A historical note. - Severn, R. T. (Earthquake engineering & structural dynamics.)
The earliest known shaking table, driven by hand-power, was constructed in Japan at the end of the 19th century. At the beginning of the 20th century developments had moved to the Stanford University in the U.S. with the introduction of an electric motor to produce a more refined oscillatory motion in one direction, the response of the testpiece being recorded mechanically by pens on a rotating drum. Major earthquakes in the 1920s prompted renewed interest at Stanford resulting in a uni-directional table moving on rails, activated either by a pendulum striking at one end?the other being resisted by springs?or by a wheel with an eccentric-mass attached to the table. A valuable feature here was that the size of the eccentric mass could be varied as the harmonic motion continued, thereby providing a method of control. In the 1950s, a similar pendulum input was used on a table constructed at the University of California, but instead of rails, it was supported by a group of vertical bars flexible in one direction only, and the 1939?1945 war had resulted in the availability of electrical devices for measuring response. Also, in Italy at this time the use of pendulums was augmented by contra-rotating mass input devices giving better frequency control; arrays of several electrodynamic exciters were also used. In Japan, motion was induced by the release of compressed springs. The idea of producing input by an oil-filled piston was introduced at MIT after the 1933 Long Beach earthquake to a table suspended from above by wires. Two other innovations here were of the greatest significance. First was an analogue device for using an actual earthquake record as input, and the second was control of the motion by an error-driven electrically controlled feedback loop. The development of these ideas into the shaking tables, which we use today, had to wait upon the general development of control engineering during the 1939?1945 war, followed by progressively greater speeds in digital computation. This history ends (c.1985) after the continuation of these advances made possible full 6-DOF control using many oil-filled actuators, but before they became able to give us real-time control with the attendant abilities of multi-support input and the experimental study of inelastic behaviour.